Supratentorial neurenteric cyst associated with a intraparenchymal subependymoma. (13th August 2012) - Natrella, Francesco; Mariottini, Aldo; Rocchi, Raffaele; Miracco, Clelia
Abstract : Neurenteric cyst is a rare developmental lesion that very infrequently is localised supratentorially. Intraparenchymal subependymoma is an even more rare benign tumour. The authors report the case of a 45-year-old gentleman with a background of drug resistant epilepsy. An MRI was performed which showed a left frontal cystic lesion with a solid component. Histopathology confirmed a type C neurenteric cyst associated with an intraparenchymal subependymoma. Following enlargement of the lesion and worsening of symptoms he was referred to our institution for further management. A frontotemporal craniotomy was performed for excision of the lesion but recurrence occurred within 1 year. The lesion was further excised and 19 months post re-excision the patient is seizure free with no evidence of recurrence on MRI.